Inflamação e resposta imune inata: Participação das lipoproteínas de altadensidade] [Inflamación y respuesta inmune innata: Participación de las lipoproteínas de alta densidad (2017)
The main function of high-density lipoproteins (HDL) is to transport the excess of cholesterol from tissues to the liver, where it is excreted, thus decreasing the risk of atherosclerotic plaques development and cardiovascular diseases establishment. Besides, HDL participates in different processes of the immune response, as its components have anti-inflammatory, anti-oxidative and anti-apoptotic activities, among others. At cellular level, these lipoproteins have the ability to modify lipid rafts, critical micro-domains that participate in signaling pathways in response to pathogens. Likewise, it has been reported that HDL have a great impact in sepsis, as they eliminate the excess of LPS in blood and transport it to the liver for its elimination, and downregulate the expression of TLR4, main receptor of this molecule. Also, HDL can modulate humoral innate immune responses through regulating the activation of the complement pathway and the expression of pentraxin 3, resulting in the modulation of inflammatory processes. In fact, it has been reported that in several infectious diseases, atherosclerosis and sepsis, the level and function of HDL are altered, which associates with the progress of the diseases. © 2017, Universidad de Antioquia. All rights reserved.